Giant retroperitoneal lipoma: a case report and literature review - Habib, Dato O.; Mkira, Omar; Kamil, Mohamed A.; Kaid, Kaid M.; Moctar, Noufou F.; Belkouchi, Omar; Malki, Hadj O. El (International Surgery Journal, 2026)
Retroperitoneal lipomas are exceptionally rare benign tumors, with fewer than 20 cases documented over the past four decades. We present a case of a giant retroperitoneal lipoma managed surgically to highlight the diagnostic and therapeutic considerations. A 58-year-old woman presented with a slowly enlarging abdominal mass and pain. Imaging revealed a 16-cm encapsulated retroperitoneal mass originating in the left iliopsoas muscle consistent with a lipoma. The concurrent findings included an ovarian cyst and an umbilical hernia. The patient underwent resection involving a transperitoneal laparotomy with capsular preservation. Histopathology confirmed a mature lipocytic lipoma without malignancy. This case reinforces the understanding that retroperitoneal lipomas, though rare, require meticulous preoperative evaluation with magnetic resonance imaging to distinguish them from liposarcomas. Complete surgical excision remains the gold standard in terms of yielding excellent outcomes. The documentation of such cases is crucial to expand the understanding of this rare pathology.